A cross-sectional examination of choice and behavior of veterans with access to free medicinal cannabis. (3rd September 2019) - Loflin, Mallory J E; Babson, Kimberly; Sottile, James; Norman, Sonya B; Gruber, Staci; Bonn-Miller, Marcel O
ABSTRACT: Background: With a rise in public pressure to increase veteran access to medicinal cannabis, free cannabis collectives for military veterans are proliferating across the US. Objectives: The aim of the current study was to document which cannabis formulations and routes of administration are chosen by veterans with increased access to cannabis, and to determine whether cannabis is being used as a substitute for other licit and illicit drugs. Method: The current study collected cross-sectional self-report data on cannabis use, cannabinoid constituent composition, primary indication of use, and substitution practices among a sample of 93 US military veterans (84.9% male) with access to free cannabis. Result: Most of the sample reported using cannabinoids as a substitute for either alcohol, tobacco, prescription medications, or illicit substances, reported that they use cannabis frequently (Modal frequency >4x/day, Modal quantity = 5 to 8 grams/week), and primarily select higher-risk cannabis formulations (i.e., high THC/low CBD, smoked). The majority of the sample reported that they use cannabis to self-treat multiple physical and mental health conditions/symptoms. Conclusions: Results of the current study suggest that military Veterans with reduced barriers to access cannabis could be making both helpful and harmful choices regarding their cannabis use. These findings suggest that more guidance on the selection of cannabis-based products in this population is warranted, particularly as barriers to medicinal cannabis access are reduced.